Health system responsiveness and its associated factors for intrapartum care in conflict affected areas in Amhara region, Ethiopia: a cross-sectional study - Asmamaw Atnafu; Endalkachew Dellie; Adane Kebede; Wubshet Debebe Negash; Samrawit Mihret Fetene; Tsegaye G. Haile; Melaku Birhanu Alemu; Jinha Park; Selamawit Tefera; Bruhtesfa Mouhabew Alene (BMJ Open, 2024)
Objective In Ethiopia, information about health system responsiveness (HSR) in conflict-affected areas is limited. No previous local study was conducted on the assessment of HSR at the community level. Hence, the study assessed HSR for intrapartum care in conflict-affected areas in Amhara region, Ethiopia.Design Community-based cross-sectional study design.Setting Wadila, Gayint and Meket districts, Amhara region, Ethiopia.Participants The participants were 419 mothers who gave birth in conflict-affected areas within the last 6 months. The study included all mothers who gave birth at health facilities but excluded those who delivered at home, critically ill or unable to hear.Outcome HSR was the outcome variable. In this regard, the study assessed how mothers were treated and the situation in which they were cared for in relation to their experience during the conflict.Methods We conducted the study in the community, where we analysed eight domains of HSR to identify 30 measurement items related to intrapartum care responsiveness. The domains we looked at were dignity (4), autonomy (4), confidentiality (2), communication (5), prompt attention (5), social support (3), choice (3) and basic amenities (4). We used a multiple linear regression model to analyse the data, and in this model, we used an unstandardized β coefficient with a 95% CI and a p value of less than 0.05 to determine the factors significantly associated with HSR.Results The findings of our study revealed that the overall proportion of HSR in intrapartum care was 45.11% (95% CI: 40.38 to 49.92). The performance of responsiveness was the lowest in the autonomy, choice and prompt attention domains at 35.5%, 49.4% and 52.0%, respectively. Mothers living in urban areas (β=4.28; 95% CI: 2.06 to 6.50), government employees (β=4.99; 95% CI: 0.51 to 9.48), those mothers stayed at the health facilities before delivery/during conflict (β=0.22; 95% CI: 0.09 to 0.35), those who were satisfied with the healthcare service (β=0.69; 95% CI: 0.08 to 1.30) and those who perceived the quality of healthcare favourable (β=0.96; 95% CI: 0.72 to 1.19) were more likely to rate HSR positively. On the other hand, joint decision-making for health (β=−2.46; 95% CI: −4.81 to –0.10) and hospital delivery (β=−3.62; 95% CI: −5.60 to –1.63) were negatively associated with HSR.Conclusion In the Amhara region of Ethiopia, over 50% of mothers living in areas affected by conflict reported that health systems were not responsive with respect to intrapartum care. Therefore, all stakeholders should work together to ensure that intrapartum care is responsive to conflict-affected areas, with a focus on providing women autonomy and choice.